Decentralization and Grassroots Development: Local Participation and Administrative Efficiency in Village Fund Management in Eastern Indonesia - Zalili, Iana; Soselisa, Pieter Sammy; Patty, Julia Theresia (Baileo: Jurnal Sosial Humaniora, 2023)
This article aims to evaluate the utilization of Village Funds in the implementation of development programs in Poka Village, Teluk Ambon District, as part of the broader dynamics of decentralization and grassroots development in Eastern Indonesia. The study focuses on local participation and administrative efficiency in managing Village Funds. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews, and documentation. Ten purposively selected informants represented various key stakeholders within the village. Data analysis followed Miles and Huberman’s interactive model, involving data reduction, data display, and conclusion drawing. The findings indicate that the use of Village Funds in Poka Village has been effective, as evidenced by the high realization rate of development programs and adherence to plans formulated through participatory village planning forums. Community involvement throughout planning and implementation reflects a relatively strong participatory model, although challenges remain in terms of administrative capacity and consistent reporting. The novelty of this study lies in its emphasis on the relationship between fiscal decentralization structures and local participation dynamics in Eastern Indonesia—a region often overlooked in rural development literature. The study recommends strengthening village governance capacity and promoting more systematic community involvement to improve fund management effectiveness.